The dialectic of democracy: modernization, emancipation and the great regression. Issue 3 (2nd April 2020) - Blühdorn, Ingolfur
ABSTRACT: In some of the most established and supposedly immutable liberal democracies, diverse social groups are losing confidence not only in established democratic institutions, but in the idea of liberal representative democracy itself. Meanwhile, an illiberal and anti-egalitarian transformation of democracy evolves at an apparently unstoppable pace. This democratic fatigue syndrome, the present article suggests, is qualitatively different from the crises of democracy which have been debated for some considerable time. Focusing on mature democracies underpinned by the ideational tradition of European Enlightenment, the article theorizes this syndrome and the striking transformation of democracy in terms of a dialectic process in which the very norm that once gave birth to the democratic project – the modernist idea of the autonomous subject – metamorphoses into its gravedigger, or at least into the driver of its radical reformulation. The article further develops aspects of my existing work on second-order emancipation and simulative democracy . Taking a theoretical rather than empirical approach, it aims to provide a conceptual framework for more empirically oriented analyses of changing forms of political articulation and participation.